2021
DOI: 10.18632/aging.202819
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and peripheral immunocyte subsets alteration of 85 COVID-19 deaths

Abstract: Objectives: To retrospectively evaluate the clinical and immunological characteristics of patients who died of COVID-19 and to identify patients at high risk of death at an early stage and reduce their mortality. Results: Total white blood cell count, neutrophil count and C-reactive protein were significantly higher in patients who died of COVID-19 than those who recovered from it (p < 0.05), but the total lymphocyte count, CD4 + T cells, CD8 + T cells, B cells and natural killer cells were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The condition of severe patients with COVID-19 is critical and can change rapidly (23). Our results demonstrated that the white blood cell count, neutrophil count, and lymphocyte count were signi cantly lower in the severe group than in the mild group, suggesting that early diagnosis and intervention are very important to reduce the risk of death caused by the tendency to severe condition transformation (24). A study comparing the virus shedding time between patients hospitalized in ICU and those not hospitalized in ICU, showed that the duration of virus shedding time of blood, saliva, and nasal samples was longer in ICU patients than in non-ICU patients (25).…”
Section: Discussionmentioning
confidence: 64%
“…The condition of severe patients with COVID-19 is critical and can change rapidly (23). Our results demonstrated that the white blood cell count, neutrophil count, and lymphocyte count were signi cantly lower in the severe group than in the mild group, suggesting that early diagnosis and intervention are very important to reduce the risk of death caused by the tendency to severe condition transformation (24). A study comparing the virus shedding time between patients hospitalized in ICU and those not hospitalized in ICU, showed that the duration of virus shedding time of blood, saliva, and nasal samples was longer in ICU patients than in non-ICU patients (25).…”
Section: Discussionmentioning
confidence: 64%
“…The condition of severe patients with COVID-19 is critical and can change rapidly. Our results demonstrated that the white blood cell count, neutrophil count, and lymphocyte count were significantly lower in the severe group than in the mild group, suggesting that early diagnosis and intervention are very important to reduce the risk of death caused by the tendency to severe condition transformation ( 26 ). A study comparing the virus shedding time between patients hospitalized in the ICU and those not hospitalized in the ICU showed that the duration of virus shedding time of blood, saliva, and nasal samples was longer in ICU patients than in non-ICU patients ( 27 ).…”
Section: Discussionmentioning
confidence: 75%
“…Focusing on T-cell subsets, several studies have highlighted the role of T-lymphocyte subset absolute counts assessed at hospitalization in predicting the risk of death in COVID-19 patients. Xiong L. et al evaluated lymphocyte subsets in 85 COVID-19 fatal cases and found that an increase in neutrophils absolute count and a decrease in CD4+ T-cell absolute count were independent risk factors for mortality [ 22 ]. Overall, in our population, median CD3+, CD3+CD4+, and CD3+CD8+ T-lymphocyte absolute counts were reduced, while CD19+ B-lymphocyte and CD3negCD16+CD56+ NK-cell absolute counts were within laboratory normality ranges.…”
Section: Discussionmentioning
confidence: 99%